Introduction: Gender and judging in the Middle East and Africa - Monika Lindbekk; Rania Maktabi (Oñati Socio-Legal Series)
Since the turn of the millennium, the appointment of women judges has increased markedly in Africa and the Middle East, along with the social and political influence of courts. The expansion of judicial power worldwide raises important questions about who the judges are and what their role should be. The appointment of women to positions of judicial authority has increased, but this increase is only beginning to be reflected in socio-legal studies. The articles collected in this special issue contribute to the burgeoning empirical comparative literature by approaching the subject matter from two analytical angles: (i) Gendered patterns in judicial selection processes that focus mainly on judicial selection processes and subsequent legal careers; and (ii) Gendered aspects of court practices that shed light on whether and how gender plays into judging practices and experiences at court. The authors in this special volume elaborate on the theme of gender and judging predominantly through one of these two analytical entries with case studies on Tunisia, Ghana, Syria, Kuwait, and the other five oil-rich Gulf monarchies.